Mathematical Design of the Experiment in the Development of Technology of Beeswax obtaining from Propolis - Oleg Shpychak (Journal of Global Pharma Technology, 2018)
In present material the development of the technology of purified beeswax obtaining from propolis, which meets modern physical-chemical and therapeutic requirements, using a various models of mathematical design of the experiment has been shown.In this work a petroleum-ether fraction of propolis containing a beeswax products was used. While analyzing of the obtained fraction, lipids and some other high-molecular compounds of unqualified structure are extracted in parallel, as well as an insignificant number of the γ-pyrone derivatives.In this connection, the development of the condition of beeswax obtaining from this fraction, which is maximally purified from the related substances was reasonable. For this purpose a series of classical methods of fractionally differentiated extraction followed by fractions evaporation in a vacuum was used. In addition, methods of precipitation using a some organic solvents were used.The optimal conditions of the technology of purified beeswax obtaining from propolis have been determined by methods of mathematical design.Keywords: propolis, beeswax, technology, methods of fractionally differentiated extraction, precipitation, methods of mathematical design.